A Study of Discourse System of National Image Construction - Xiaobo, Liang; Juling, Tan (Sinología hispánica. China Studies Review, 2017)
The construction of discourse is indispensable to the construction of national image to a large extent, particularly a set of discourse built from various perspectives. It must pertain to the real fact of the country and to the needs of her future development. More importantly, it must be effective. Considering the characteristics of the national image and its construction discourse, the discourse system of our country’s national image needs, first of all, to have a good treatment of the core characteristics of our country’s national image; meanwhile, it also needs to have a good handling of the basic characteristics of our country’s national image. Specifically speaking, it is necessary to take in account of factors like ethnicity, culture, politics, space-time and cognition of national image discourse for one thing; it is also necessary to take into account such factors as stability, multi-dimension, inheritance and creation, and the crisis coordination of national image discourse for another.